Stephen Jay Gould : reflections on his view of life - Allmon, Warren D.; Kelley, Patricia H.; Ross, Robert M. (Robert Merrill), 1963- (Oxford University Press, 2009)
Considered by many during his lifetime as the most well-known scientist in the world, Stephen Jay Gould left an enormous and influential body of work. A Harvard professor of paleontology, evolutionary biology, and the history of science, Gould provided major insights into our understanding of the history of life. He helped to reinvigorate paleontology, launch macroevolution on a new course, and provide a context in which the biological developmental stages of an organism's embryonic growth could be integrated into an understanding of evolution. This book is a set of reflections on the many are.